Highly red-shifted NIR emission from a novel anthracene conjugated polymer backbone containing Pt(ii) porphyrins. Issue 3 (8th December 2015) - Freeman, D. M. E.; Minotto, A.; Duffy, W.; Fallon, K. J.; McCulloch, I.; Cacialli, F.; Bronstein, H.
Abstract : We present the synthesis of a novel diphenylanthracene (DPA) based semiconducting polymer. Abstract : We present the synthesis of a novel diphenylanthracene (DPA) based semiconducting polymer. The polymer is solubilised by alkoxy groups attached directly to a DPA monomer, meaning the choice of co-monomer is not limited to exclusively highly solubilising moieties. Interestingly, the polymer shows a red-shifted elecroluminescence maximum (510 nm) when compared to its photoluminescence maximum (450 nm) which we attribute to excimer formation. The novel polymer was utilised as a host for a covalently-linked platinum(ii ) complexed porphyrin dopant. Emission from these polymers was observed in the NIR and again showed almost a 100 nm red shift from photoluminescence to electroluminescence. This work demonstrates that utilising highly aggregating host materials is an effective tool for inducing red-shifted emission in OLEDs.